Sustainability-based comparative stability of oxaliplatin plus leucovorin and 5-fluorouracil in infusion bags with application to plasma and colonic media samples - Hadir M. Maher; Salma Mahmoud Mohamed; Ekram M. Hassan; Amira Fawzy El-Yazbi (Scientific Reports)
Abstract FOLFOX is widely used in the treatment of colon cancer. The combination of oxaliplatin (OXA), 5-fluorouracil (5-FU), and leucovorin (LV) is administrated according to strict protocols. Based on incompatibility studies, LV and OXA are supplied concurrently via intravenous infusion, followed by intravenous administration of 5-FU. This study aims at determining the stability of the binary mixture of OXA and LV diluted in infusion bags containing either 5% dextrose or normal saline compared with their single solutions besides single solutions of 5-FU at two temperatures (room temperature and refrigeration) for two weeks. HPLC diode array detection method was developed and validated to simultaneously determine the three drugs. Stability studies in 5% dextrose solution revealed that mixtures of OXA and LV kept at room temperature showed chemical degradation for OXA, with better stability for refrigerated solutions. Generally, single solutions showed considerable stability. Using normal saline, a combination of OXA/LV showed relative stability of LV over the 15 days of study with marked degradation of OXA. 5-FU was relatively stable in 5% dextrose and normal saline at both temperatures. Method’s applicability was extended to the determination of the cited drugs in plasma and colonic media samples. Method’s sustainability, blueness, and whiteness were investigated.